Конституційні функції прокуратури України - Сінозацька, Юлія Миколаївна (My University, 2009)
Розглядаються конституційні функції прокуратури України. The constitutional functions of the Prosecutor's Office of Ukraine are considered.
Keywords: прокуратура; prosecutor's office; constitutional functions; Україна; Ukraine; Ukraine